An anxiety management intervention for people with substance use disorders (ITASUD): An intervention mapping approach based on Peplau's theory - Caroline Figueira Pereira; Divane de Vargas; Linda S. Beeber (Frontiers Media S.A., 2023)
BackgroundThe comorbidity of anxiety and drug use disorders complicates treatment prognosis, and one of the greatest challenges is to address the environmental and behavioral factors involved. The aim of this study was to describe the uses of intervention mapping in the design of a theory and evidence-based complex intervention to develop skills around the management of anxiety for cocaine users in outpatient addiction treatment.MethodsThe six steps of the intervention mapping approach, which are needs assessment, creation of matrices of performance objectives, selection of methods and practical strategies, program development, adoption and implementation, and evaluation were applied to develop the Interpersonal Theory of nursing to Anxiety management in people with Substance Use Disorders (ITASUD) intervention. The theory used for the conceptual model was interpersonal relations theory. All theory-based methods and practical applications were developed at the individual level, acting in behavioral, interpersonal, organizational and community environments.ResultsThe intervention mapping provided a broad overview of the problem and outcome expectations. The ITASUD intervention consists of five consecutive sessions of 110-min targeting individual determinants of anxiety (knowledge, triggers, relief behaviors, self-efficacy and relations), delivered by a trained nurse using Peplau's concepts of interpersonal relations. Intervention Mapping is a multi-step process that incorporates theory, evidence, and stakeholder perspectives to ensure that implementation strategies effectively address key determinants of change.ConclusionsThe intervention mapping approach increases the effectiveness of the intervention since the matrices provide a broad view of all factors that affect the problem and facilitate replication through transparency of the determinants, methods, and applications used. ITASUD addresses all factors that play an important role in substance use disorders based on a theoretical basis, which provides the translation of evidence from research into effective practice, policy, and public health improvements.